Restorative memorials: improving mental health by re-minding - Hundley, Anne (Kansas State University, 2013)
Human nature compels us to remember the past. A society’s collective memory creates meaning in our lives, establishing individual and group identity and contextualizing cultural values. Commemorative landscapes give physical form to loss and memory, providing a space for public awareness and remembrance while acting as a sanctuary for dealing with loss. Over time, memorials face a loss of relevance as generations pass and society evolves to embody different shared memories and values. At the same time, our environment directly affects our physical and psychological well-being. Restorative environments benefit the individual by reducing stress. If the well-being of the individual and his or her environment are directly linked, landscape architecture can be utilized to restore mental well-being. A commemorative space combining the characteristics of memorials and restorative environments will act as a “restorative memorial”. Beyond remembering the events, people, or circumstances that establish cultural identity and values, restorative memorials would improve mental well-being, reminding the individual of their cultural identity while reducing psychological stress. Synthesizing literature understanding the importance of memorials, restorative environments, loss, stress, and environmental psychology with experiential observations of memorials and restorative environments generated a set of design guidelines for restorative memorials. These design guidelines were applied to a design commemorating the legacy of the Menninger Clinic in Topeka, Kansas. The Menninger family formed the first group psychiatric practice in the country. They became world-renowned leaders in psychiatric and behavioral health treatments, believing a patient’s physical and social environment was instrumental to improve mental health. In 2003, the Menninger Clinic relocated to Houston, Texas, vacating a campus which played a great role in the history of Topeka, Kansas, and psychiatry. A restorative memorial commemorating the Menninger legacy could reconnect the citizens of Topeka with the history of the former campus and would pay homage to the ideals of the Menningers, using the designed environment to continue improving mental health. Restorative memorials can become landmarks in the urban fabric, providing an engaging built environment, imbued with meaning. They will transcend generational significance, serving the past, present, and future.
Keywords: Memorials; Restorative environments; Commemoration; Menninger Clinic; History of psychiatry; Topeka; Landscape Architecture (0390)